The conceptional system of orchestration in the works of European and American authors of the 19th and 20th centuries - Bohatyrov, Volodymyr (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
Relevance of the study. A review of sources on the theory of orchestration is necessary because the knowledge of this art is extensive. This issue is complicated by the fact that each of the musical traditions (including English, American, French, German, Polish and Ukrainian) has its own terminological system, which may not always be consistent. Analysing the concepts of orchestration from the linguistic and historical perspectives allows us to form a unified system that can be used in educational and musicological discourse. Main objective of the study is to analyze and systematize the basic concepts of orchestration and instrumentation in treatises and manuals written by composers and teachers, which representing different musical traditions. The methodological basis of the study is based on sourced research method (to study various sources on orchestration and instrumentation), the historical method (to determine the evolution of concepts within the orchestration system in various musicological studies), and the comparative method (to compare similar concepts in the English, German, French, Polish, and Ukrainian musical traditions). Results and conclusions. The comparing of the concepts of orchestration in different musical traditions, specifically in English, German, French, Polish, and Ukrainian contexts reveals both similarities and differences in how key terms related to orchestration are understood. The terms such as sound, tone, color, timbre, range, register, texture, density, clarity, and sonority, which collectively form the modern system of orchestration. While these terms are generally interpreted similarly across different traditions, there are subtle differences rooted in the historical and cultural contexts in which the treatises, textbooks, and manuals were created. The main differences include how musical sound and tone are defined, with some traditions, like American, Polish, and Ukrainian, considering sound as a complex concept that includes pitch, duration, loudness, and timbre. In contrast, German sources distinguish between two terms, where «klang» emphasizes timbral qualities, and «ton» is a more general term. French sources, meanwhile, differentiate between «son» as the acoustic quality of an instrument and «ton» as referring to pitch and key. Timbral characteristics are crucial in German sources, which see timbre as a defining quality of an instrument and the various transformations of sound achievable through different techniques. French, Polish, and Ukrainian authors, however, often view timbre as adding emotional and expressive content to a piece. The term «color» refers to the unique acoustic atmosphere created by specific instrumental combinations, a definition that is shared across all traditions. Texture is another key concept analyzed, defined as the morphological structure of the music. While English sources often associate texture with orchestral structure and distribution of musical lines, German focus on register and timbre, which influence the clarity and density of orchestral texture. French authors emphasize the interplay between instruments and the relationships between their parts, including dynamic and timbral transitions. In polish sources, texture describes as the organization of sound layers, with each instrumental voice interacting with others. The concepts of clarity, density, and sonority are also explored, with clarity being the result of organized sound and structural control, particularly through rhythm, harmony, and timbre. Density, on the other hand, refers to the saturation of orchestral sound, created by instrument combinations and register shifts, which enhances the quality of the sound. Finally, sonority refers to the richness and fullness of texture, influenced by the movement of voices and timbral qualities, particularly in terms of register and dynamic shading The study concludes that while there are shared definitions, each tradition offers a unique perspective on orchestration, influenced by cultural, linguistic, and historical factors. These insights are valuable for both understanding and teaching orchestration, especially in the context of modern compositions. Future research could apply these concepts to analyze contemporary orchestral works, providing a tool for understanding current orchestration practices.